Combined Administration of Curcumin and Chondroitin Sulfate Alleviates Cartilage Injury and Inflammation via NF-κB Pathway in Knee Osteoarthritis Rats - Guan, Ting; Ding, Liu-Gang; Lu, Bao-Yuan; Guo, Jia-Yi; Wu, Mei-Yin; Tan, Zhi-Qun; Hou, Shao-Zhen (Frontiers in Pharmacology, 2022)
Objective: Osteoarthritis (OA) is a degenerative chronic disease that most often occurs in the knee joint. Studies have shown that some food supplements, such as curcumin and chondroitin sulfate, are effective in treating knee osteoarthritis (KOA) by exhibiting different protective effects. In this study, we further investigated the combined therapeutic effects of curcumin and chondroitin sulfate on cartilage injury in rats with arthritis. Methods: An experimental KOA model was induced by monosodium iodoacetate (MIA) in rats. All rats were randomly divided into five groups: Ctrl (control), model (saline), Cur (20 mg/kg curcumin in saline), CS (100 mg/kg chondroitin sulfate in saline), and CA (20 mg/kg curcumin and 100 mg/kg chondroitin sulfate in saline); drugs were given 2 weeks after MIA injection. The histomorphological changes of cartilage were observed by safranin fast green staining, H&E staining, and micro-CT scanning. Also, the levels of PGE2, TNF-α and IL-1β in the arthral fluid and serum were determined by the ELISA kits. The activities of SOD, CAT, COMP, MMP-3, and type II collagen were detected by biochemical kits. The expressions of TLR4, p-NF-κB, NF-κB, and COX-2 in cartilage were detected by Western blot. Results: Data show that serum levels of IL-1β (p < 0.05), SOD (p < 0.0001), and MMP-3 (p < 0.001) were downregulated significantly in the CA group when compared to those in the model group. Meanwhile, obvious repair of cartilage with higher contains collagen II (p < 0.0001) could be observed in the CA group than the ones in Cur or CS group. In addition, significant downregulation of the expression of p-p65/p65 (p < 0.05) was found in the CA group. Conclusion: Our findings showed that combined administration of curcumin and chondroitin sulfate could exert better repair for KOA in rat models. This may hold great promise for discovering potential drugs to treat KOA and may improve treatment options for it.